2009
DOI: 10.1111/j.1439-0426.2009.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a marine protected area on fish assemblage associated withPosidonia oceanicaseagrass beds: temporal and depth variations

Abstract: This study describes the changes in the structure of the fish assemblage associated with Posidonia oceanica meadows after the establishment of a marine protected area. The survey of the ichthyofauna in the Marine Reserve of Tabarca Island was carried out by visual censuses with SCUBA. Inside and outside the reserve was sampled six times at random from summer 1997 to summer 1999 and in three different depths (1, 5 and 15 m) by applying transects of 150 · 5 m over the P. oceanica meadows. The data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…At low speeds, mobile species tend to be overestimated, whereas at faster speeds, small cryptic fish tend to be underestimated (Valle and Bayle-Sempere 2009). In the present study, the abundances of the small, cryptic and mobile taxa were significantly higher in diver UVCs than when video-based techniques were used, probably because the video techniques share these limitations or present their own biases (Harvey et al 2001;Stoner et al 2008;Longo and Floeter 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At low speeds, mobile species tend to be overestimated, whereas at faster speeds, small cryptic fish tend to be underestimated (Valle and Bayle-Sempere 2009). In the present study, the abundances of the small, cryptic and mobile taxa were significantly higher in diver UVCs than when video-based techniques were used, probably because the video techniques share these limitations or present their own biases (Harvey et al 2001;Stoner et al 2008;Longo and Floeter 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dentex dentex is a demersal sparid fish found from 0 to 200 m depth, living on various substrates such as Posidonia oceanica meadows, rocky bottom with P. oceanica patches, coastal detritic areas, ripples of coarse sand, sandy habitats with Caulerpa and Cymodocea and in the coralligenous community (Ramos-Esplà and Bayle-Sempere 1991; Abellán 2000; Guidetti 2000; Rueda and Martinez 2001;Ballesteros 2006;Stobart et al 2012). Juveniles of common dentex (20-50 mm TL, during June-August) inhabit shallow water (2-4 m depth), at the edge between Posidonia oceanica meadows and sand, or close to crevices and small caves (Dulčić et al 2002;Valle and Bayle-Sempere 2009). From the perspective of behavioural ecology, the juveniles are gregarious; observations of shoals of Dentex dentex have been made, with individuals of medium size (1-5 kg) especially in summer around rocky outcrops at depths between 20 and 50 m, but also found in shallow waters (−8 to −10 m) (Bauchot and Hureau 1986;Bayle-Sempere et al 1991;Ramos-Esplà and Bayle-Sempere 1991;Francour 1994;Chemmam-Abdelkader 2004;Sahyoun et al 2013).…”
Section: Distribution and Habitatmentioning
confidence: 99%
“…These studies showed that in the sublittoral rocky habitats of the TMPA, fish (including amphipod feeders such as Sciaena umbra and Diplodus vulgaris) biomass and/or density is up to three times greater inside fully protected areas than in partially protected areas. In P. oceanica meadows, several authors have reported that large piscivorous and invertebrate-feeding fishes are generally present in greater abundance and diversity in fully protected areas than in partially protected and unprotected areas (Francour 2000;Macpherson et al 2002;Valle and Bayle-Sempere 2009). The lower densities of several amphipod taxa that are associated with P. oceanica meadows in the fully protected areas relative to the partially protected areas of the TMPA (Sturaro et al 2014), may have been associated with a higher fish predation intensity.…”
Section: Discussionmentioning
confidence: 99%